Identidad urbana: estrategia para la reconfiguración del espacio público en grandes nodos de transporte (2022)
Mobility and urban transport are configured as an essential part in the displacement and interaction of the population with the various social scenarios related to urban life, however the spaces in which mobility nodes are presented are configured following certain parameters and guidelines, in such a way that they present a lack of appropriation and identity of the space, that is why it is based on a planning that arises from the relationship with the pedestrian and the human scale, guaranteeing access and circulation to the largest number of the population in an inclusive, efficient and diverse and interconnected and an efficient interaction between the various modes of transport (urban intermodality), for this reason the planning and configuration of public space is focused on the urban transport node with the greatest projection in the city of Bogotá (metro station calle 72) which relates the metro system, Transmilenio and regiotram with alternative transport lanes and pedestrian axes onals in the perimeter area of ​​this station.